2002
DOI: 10.1063/1.1530739
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of local and global scaling regimes in thin films deposited by sputtering: An atomic force microscopy and electrochemical study

Abstract: The surface morphology of NiOx thin films deposited by rf sputtering was studied by atomic force microscopy and by cyclic voltammetry. Linear relationships were observed in log–log plots of the interface width versus window length and in log–log plots of the peak current versus scan rate. Two different slopes were observed, by both techniques, indicating that distinct growth dynamics present in the system can be measured in different ways. Moreover, the calculated fractal dimensions are in excellent agreement:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 12 publications
1
12
0
Order By: Relevance
“…From the obtained AFM data, it is observed that the nanosheets after selenization were rougher than the Zn 1‐ x Fe x –LDH nanosheet . Since the electrophysical–chemical properties of the material are strongly dependent on surface roughness, the as‐synthesized materials are expected to show distinct catalytic activities …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…From the obtained AFM data, it is observed that the nanosheets after selenization were rougher than the Zn 1‐ x Fe x –LDH nanosheet . Since the electrophysical–chemical properties of the material are strongly dependent on surface roughness, the as‐synthesized materials are expected to show distinct catalytic activities …”
Section: Resultsmentioning
confidence: 99%
“…[47,48] Since the electrophysical-chemical properties of the material are strongly dependent on surface roughness, the as-synthesized materials are expected to show distinct catalytic activities. [49] Further, in order to get better insights into the structuralrelated information, high-resolution transmission electron microscope (HR-TEM) was carried out.…”
Section: Structural Characterizationmentioning
confidence: 99%
“…CdTe grains are characterized by using the circularlyaveraged autocorrelation function g(r) where the averaged value for the grain's radius is obtained from the position of the first zero-crossing of g(r) (Fig. 1) [15]. The average grain radius measured is 466 ± 23 nm.…”
Section: Sem-afmmentioning
confidence: 99%
“…In fact, few studies have been conducted to quantitatively describe the relationship between surface morphology and film microstructure. Substantial amounts of efforts have been directed to the quantitative description of the morphology of rough surfaces and interfaces of thin films [6,7].…”
Section: Introductionmentioning
confidence: 99%